hexA of Erwinia carotovora ssp. carotovora strain Ecc71 negatively regulates production of RpoS and rsmB RNA, a global regulator of extracellular proteins, plant virulence and the quorum-sensing signal, N-(3-oxohexanoyl)-l-homoserine lactone - Mukherjee, Asita; Cui, Yaya; Ma, Weilei; Liu, Yang; Chatterjee, Arun K. (Environmental microbiology, 2000)
The soft‐rotting bacterium, Erwinia carotovora ssp. carotovora (E. c. carotovora ), produces an array of extracellular enzymes (= exoenzymes), including pectate lyase (Pel), polygalacturonase (Peh), cellulase (Cel) and protease (Prt), as well as HarpinEcc, the elicitor of hypersensitive reaction (HR). The production of these exoenzymes and HarpinEcc responds to plant products and the quorum‐sensing signal [N‐(3‐oxohexanoyl)‐ l‐homoserine lactone; OHL] and is subject to both transcriptional and post‐transcriptional regulation. hexA of E. c. carotovora strain Ecc71 (hereafter hexA71), like that of another E. c. carotovora strain, negatively controls the production of exoenzymes, OHL and virulence in E. c. carotovora strain Ecc71. In addition to exoenzymes, HexA71 negatively regulates the expression of hrpNEcc, the structural gene for HarpinEcc. Exoenzyme overproduction is abolished by OHL deficiency in a HexA− and OhlI − double mutant, indicating that HexA and OHL are components of a common regulatory pathway controlling exoenzyme production. HexA71 negatively affects RpoS, as the levels of this alternative sigma factor are higher in the HexA− mutant than in the HexA+ strain. However, a HexA− and RpoS− double mutant produces higher levels of exoenzymes and transcripts of pel‐1, peh‐1 and celV genes than the HexA− and RpoS+ parent. Thus, the elevated levels of RpoS protein in the HexA− mutant do not account for exoenzyme overproduction. The following evidence associates for the first time the phenotypic changes in the HexA− mutant to overproduction of rsmB RNA, a global regulator of exoenzymes, HarpinEcc, OHL and secondary metabolites. Analyses of rsmB transcripts and expression of an rsmB–lacZ operon fusion in E. c. carotovora strain Ecc71 revealed that HexA71 negatively regulates transcription of rsmB. Multiple copies of hexA71+ DNA suppress various phenotypes, including exoenzyme production in E. c. carotovora strain Ecc71, and concomitantly inhibit the production of rsmB, pel‐1, peh‐1, celV and hrpNEcc transcripts. Multiple copies of rsmB+ DNA, on the other hand, stimulate exoenzyme production by relieving the negative effects of a chromosomal copy of hexA+. The occurrence of hexA homologues and the negative effect of the dosage of hexA71 DNA on rsmB transcripts were also detected in other E. c. carotovora strains as well as Erwinia carotovora atroseptica and Erwinia carotovora betavasculorum. Extrapolating from the findings with LrhA, the Escherichia coli homologue of HexA, and the presence of sprE homologues in E. carotovora subspecies, we propose that HexA71 controls several regulatory pathways in E. carotovora including rsmB transcription and the production of SprEEcc which, in turn, affects RpoS levels. A model is presented that integrates the findings presented here and our current knowledge of the major regulatory network that controls exoprotein production in soft‐rotting Erwinia carotovora subspecies.